EXPLORING THE LINGUACULTURAL DIMENSIONS OF LIMERICKS IN ENGLISH LITERATURE (Konferensiyalar | Conferences, 2024)
Limericks, with their whimsical language and playful humor, have long captivated readers with their unique blend of linguistic creativity and cultural commentary. Originating in Ireland, these five-line poems have become a beloved form of verse in English literature, celebrated for their rhythmic cadence, clever wordplay, and satirical wit. However, beyond their surface charm lies a rich tapestry of linguacultural significance, offering insights into both the linguistic features of the English language and the cultural contexts in which limericks emerge.